Left Atrial Radiofrequency Ablation Associated with Valve Surgery: Midterm Outcomes - Nardi, Paolo; Mvondo, Charles Mve; Scafuri, Antonio; Pellegrino, Antonio; D'Auria, Francesca; Polisca, Patrizio; Zeitani, Jacob; Chiariello, Luigi (The Thoracic and Cardiovascular Surgeon, 2013)
Background Left atrial ablation is a surgical standard technique for the treatment of persistent or chronic atrial fibrillation (p-AF and c-AF, respectively).Objective The aim of the study is to evaluate midterm results of left atrial ablation according to modified Maze procedure in patients affected by p-AF or c-AF and concomitant mitral or aortic valve disease requiring surgical treatment.Methods A total of 108 patients (age, mean ± standard deviation [SD]: 66 ± 8.5 years) underwent left atrial ablation by means of unipolar (n = 62) or bipolar (n = 66) radiofrequency for p-AF (n = 28) or c-AF (n = 100) in association with mitral (n = 93) or mitral and aortic valve (n = 35) surgery.Results In-hospital mortality was 0.8%. Patients with preoperative c-AF had preoperative greater value of left atrial diameter (56.7 ± 7.4 vs. 52 ± 9 mm, p = 0.05) than those with p-AF. At 9 years after Maze procedure, 86% (n = 24/28) of patients with preoperative p-AF were in sinus rhythm versus 28% (n = 27/95) with c-AF (p < 0.0001). Preoperative c-AF and left atrial diameter of 75 mm or more predicted atrial fibrillation recurrence. In patients in sinus rhythm compared with those in residual atrial fibrillation, survival was 100 versus 86% ± 6.4%, New York Heart Association class was 1.3 ± 0.5 versus 1.7 ± 0.6, and need of lifelong anticoagulation therapy was 43 versus 91% (p < 0.05, for all comparisons).Conclusions Left atrial Maze procedure for p-AF offers better chances to conversion in sinus rhythm as compared with long-standing c-AF. Survival, functional status, and quality of life are superior in patients who benefit from sinus rhythm.
Keywords: atrial fibrillation; mitral valve surgery; aortic valve surgery; radiofrequency ablation